Republic of Benin Country Environmental Analysis - World Bank (World Bank, Washington, DC, 2020)
This report is the product of a comprehensive study on Benin. It highlights the country s geographical and economic situation and concentrates in particular on environmental conditions and the challenges facing Benin. This report covers the financing of priority environmental activities, as well as allocations to programs designed to improve the environment and living conditions of the population. The environmental analysis of Benin seeks to help the Government integrate the environment into policy formulation by analyzing cross-cutting aspects and the challenges of implementing sound environmental management, and creating a platform for strengthening the country s capacities in order to facilitate sustainable natural resource and environmental management. To this end, a number of measures have been recommended, among them the establishment of effective policies and institutions based on sound governance and improved effectiveness, and the mobilization of financing for environmental protection and natural resource management. The study includes the analysis of a case study on three cities: Porto-Novo, Cotonou, and Parakou, and examines the impact of environmental problems and environmental management challenges on these cities.